Numerical properties of a model problem for evaluation of natural tracer transport in groundwater - Hokr, Milan; Balvín, Aleš (Proceedings of the Conference Algoritmy, 2016)
We solve a model problem of natural tracer transport in groundwater between the surface and the tunnel, based on field measured data. The problem with a simplified geometry represents the main features of flow inhomogeneity, namely the presence of fractures and matrix, and an influence of the stagnant zones on the tracer breakthrough. From the fictitious pulse tracer input, we calculate the mean residence time. The problem is solved by the mixed-hybrid finite element method for the flow equation and the discontinuous Galerkin method for the advection-diffusion transport, both implemented in Flow123d open-source software. We check a convergence by the time step refinement and find the limit of the mean residence time with rising time interval. The effect of dispersion parameters can explain some of the differences between results obtained by different numerical software in a separate study [5]. We also show how both the flow and the transport problem have a simple and efficient procedure to solve their inverse problems.